THE EFFECT OF FISCAL BALANCE TRANSFER, FINANCIAL PERFORMANCE ON CAPITAL EXPENDITURE IMPACTING ON THE HUMAN DEVELOPMENT INDEX OF PAPUA PROVINCE - Bonifasia Elita Bharanti (Universitas Cenderawasih, 2019)
The structure of Regional Development Budget (hereafter APBD) of Papua Province, which is mostly sourced from Government transfers tends to increase every year. This requires prioritising the use of capital expenditure that can improve the welfare of the community. However, it is an irony that the poverty rate in Papua Province ranks first in Indonesia as indicated by the Human Development Index (HDI), below the national average HDI. The objective to analyse the structure of the APBD (General Allocation Fund - hereafter DAU, Special Allocation Fund - hereafter DAK and Revenue Sharing Fund - hereafter DBH) and financial performance of Papua's Human Development Index in 2013-2018 with capital expenditure as an intervening variable. Quantitative approach is used with secondary data type, which is processed using the IBM SPSS Amos application. This study indicate that the increasing APBD structure will be able to increase the HDI but capital expenditure does not mediate the APBD structure to the HDI. Furthermore, financial performance has no impact on increasing the HDI as the capital expenditure does not mediate financial performance on the human development index.